2018
DOI: 10.1186/s13012-017-0705-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing organizational implementation context in the education sector: confirmatory factor analysis of measures of implementation leadership, climate, and citizenship

Abstract: BackgroundA substantial literature has established the role of the inner organizational setting on the implementation of evidence-based practices in community contexts, but very little of this research has been extended to the education sector, one of the most common settings for the delivery of mental and behavioral health services to children and adolescents. The current study examined the factor structure, psychometric properties, and interrelations of an adapted set of pragmatic organizational instruments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
149
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(169 citation statements)
references
References 72 publications
18
149
1
1
Order By: Relevance
“…Overall, the strength of these findings is noteworthy given that data were collected independently, by two different investigative teams, in very different geographic areas of the U.S., and with broadly different nurse demographics. Our results contribute to the strong record of the scale’s validity and reliability in other contexts (Aarons et al, ; Aarons et al, ; Finn et al, ; Lyon et al, ; Torres et al, ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Overall, the strength of these findings is noteworthy given that data were collected independently, by two different investigative teams, in very different geographic areas of the U.S., and with broadly different nurse demographics. Our results contribute to the strong record of the scale’s validity and reliability in other contexts (Aarons et al, ; Aarons et al, ; Finn et al, ; Lyon et al, ; Torres et al, ).…”
Section: Discussionsupporting
confidence: 70%
“…The scale focuses on specific leadership behaviors enacted by frontline managers to influence implementation, including: (a) proactive leadership; (b) knowledgeable leadership; (c) supportive leadership; and (d) perseverant leadership. The ILS, originally developed and tested in mental health settings, has been cross‐validated in substance use facilities (Aarons, Ehrhart, Torres, Finn, & Roesch, ), child welfare service organizations (Finn, Torres, Ehrhart, Roesch, & Aarons, ), and education sectors (Lyon et al, ). However, it has yet to be validated for use in nursing contexts.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that this type of institutional support for evidence‐based curricula may be especially important for delivering EBPs with high fidelity. Furthermore, our results are consistent with a recent study by Lyon and colleagues, who found that a general focus on EBPs may be an important support for effective delivery . Although general support of EBPs seems to be associated with fidelity, our interview results point to less specific support for health education.…”
Section: Discussionsupporting
confidence: 91%
“…We found an association between focus on EBP and fidelity. A growing body of research recognizes the critical role implementation climate plays in the successful implementation of programs, including programs in schools . These results suggest that this type of institutional support for evidence‐based curricula may be especially important for delivering EBPs with high fidelity.…”
Section: Discussionmentioning
confidence: 99%
“…It was not clear whether this was in reference to general attitudes towards EBPs or for an identified practice change. Additionally, non‐nursing studies made mention of the impact of IL on implementation citizenship (Aarons, Ehrhart, Torres, et al, ; Finn, Torres, Ehrhart, Roesch, & Aarons, ; Lyon et al, ; Powell et al, ), which are the behaviours by staff that support EBP. These studies proposed implementation citizenship as a mediating variable between IL and implementation climate.…”
Section: Resultsmentioning
confidence: 99%